Regulation of work and employment: advances, tensions and future directions in research in international and comparative HRM. Issue 21 (30th November 2017) - Rodriguez, Jenny K.; Johnstone, Stewart; Procter, Stephen
Abstract: Changes to dynamics work and employment have resulted in calls for more sustainable management, procedural control, institutional governance, and political accountability. Against this background, there is renewed attention to regulation, its terms, nature and quality, and its role to shape the employment relationship. An important concern for international and comparative human resource management (I/CHRM) is understanding the role of regulation in interacting with these changes and how this varies across within and between countries. Regulation sits at the centre of competing economic and social demands, which are seen as both complementary and irreconcilable, and its complexity needs to be theorized and empirically mapped. The article discusses key themes related to changes to dynamics, processes and structures, and tensions that concern the fields of I/CHRM and its relationship with the regulation of work and employment. The article calls for more comprehensive insight into the theoretical links between regulation and I/CHRM, and more empirical evidence of their interplay across contexts. It suggests that engaging with the paradoxes and ambiguities of different competing agendas of regulation of work and employment, and exploring these in relation to different social actors within and across geographies is a significant step in advancing research in this area.